Flower Abscission of Chilli (Capsicum Annuum L. Var. Kulai) Under Humid Tropical Conditions and the Use of Plant Growth Regulators to Improve Fruit Set and Yield - Inuwa Shesu, Usman (1997)
A series of experiments were carried out under glasshouse and field conditions, at the Universiti Pertanian Malaysia (UPM), Serdang (latitude 3002'N and longitude 101042'E), during the period January 1994 to December 1996. The main objective of the research is to study the nature of abscission of chilli flowers and to use plant growth regulators (PGRs) to improve fruit set and yield of chilli under heat stressed tropical conditions. Most of the flowers fall 3 days after anthesis. This suggest that flower abscission under heat stress is related to the ontogenic changes taking place in the flowers at this stage (pollination and fertilization). Pollen viability and pollen tube growth were not impaired by the stress. Also seed production and viability were similar under both glasshouse and open conditions. Electron microscopic observations revealed an abscission zone between the peduncle and the twig. The first morphological evidence of abscission by way of cell separation became visible at anthesis. Energy dispersive X - ray scan of this zone showed higher accumulation of Ca2+ relative to the surrounding areas. The visibility of cell separation at anthesis indicated that the process of abscission begun prior to pollination and fertilisation. Endogenous hormone analysis in abscising chilli flowers showed that peak production of ethylene and its precursor 1- aminocyclopropane- lcarboxylic acid (ACC) was at anthesis. Similarly, highest levels of indole acetic acid (IAA) were detected at this stage. The level of abscissic acid (ABA) increased with advancement of abscission. On the use of PGRs to improve fruit set and yield of chilli, naphthalene acetic acid (NAA), paclobutrazol (PP333), gibberellic acid (GA4+7), and triacontanol (TRIA) were applied to pot grown chilli plants. The GA4+7 treatment proved superior over other PGRs in flower count, fruit count, fruit size and total fruit yield. The yield increase following NAA application has not been consistent. The application of TRIA proved effective only in the open. PP333 application increased fruit set and gave the least recorded abscission. In addition this treatment gave yields that are comparable to other PGRs. GA4+7 and PP333 were selected for the next stage of the study.